The greatness guide. - Sharma, Robin S. (Robin Shilp), 1964-; Verner, Adam (Highbridge Audio, 2018)
Tired of playing small with your life' Feel like you were meant to be so much more' Ready to become spectacularly successful, breathtakingly effective and wildly fulfilled as you work and live at a level called extraordinary' Passionate, inspiring, provocative and full of big ideas that will get you to your ideal life faster than you've ever imagined, The Greatness Guide and The Greatness Guide Book 2 are those rare books that truly have the power to release your potential and awaken your best self. The Greatness Guide Book 2 offers more of Robin's inspiring anecdotes, tips and big ideas. Discover ideas to generate wealth and energy, tool kits for practical work-life balance, time-management techniques that really work, practical strategies to turn setbacks into opportunities and so much more. The Greatness Guide Book 2 will uplift, energize and move you to action.